Analysis of The Implementation Of Patient Safety Targets In Professional Health Care at 3M Plus Tembilahan Hospital - Nelli Adelia Resmalita; Ermi Girsang; Sri Lestari Ramadhani Nasyushan (Eduvest - Journal of Universal Studies, 2024)
Patient safety is an important factor for everyone, especially in the health system. The importance of patient safety, considering the magnitude of the problem that exists for patients and health care professionals. The role of professional health care is very important to improve the quality of services provided and improve or ensure patient safety. The importance of patient safety is increasingly prioritized around the world and every day health care professionals face several challenges in providing safe care to patients. This study aims to analyze the application of patient safety goals in health care professionals at 3M Plus Tembilahan Hospital. The type of research is quantitative analysis using a cross sectional study approach. The research sample was carried out using the total sampling method, namely 201 respondents at 3M Plus Tembilahan Hospital. The data was analyzed using Partial Least Square (PLS). The results of the study showed that there was a relationship of analysis of the implementation of patient safety goals in health care professionals at 3M Plus Tembilahan Hospital.